Survey of the Implementation of Grammar Translation Method (GTM) In Teaching Vocabulary and Grammar to the First Year Students of Al – Islam Kartasura Junior High School In 2023/2024 Academic Year - Handayani, Sri; Sujito, Sujito (English Education and Literature Journal (E-Jou), 2025)
Grammar Translation Method (GTM) as a traditional method can improve the vocabularies of students. The topic of this research is The Implementation of Grammar Translation Method in Teaching Vocabulary and Grammar to the First Year Students of Al - Islam Kartasura Junior High School in 2023/2024 Academic Year. The population are seventy students of first grade and the sampling in this research is first grade or class 7A of Al - Islam Kartasura about twenty students. The teacher gives pretest and posttest. The researcher also using questioners and interview each student. The reason of this research is because the student’s score of vocabulary and grammar skill in the Al - Islam Kartasura is bad. The problem in this class are low motivation and low score in English language especially in grammar and vocabulary. So, the objective of this research was to find how the Grammar Translation Method can improve students’ grammar and vocabulary mastery to the First Year Students of Al - Islam Kartasura Junior High School in 2023/2024 Academic Year and whether the grammar translation method can be used as a method in improving the students’ achievement of grammar and vocabulary mastery. The researcher uses Grammar Translation Method to treatment that class. Grammar Translation Method is very effective for the students although it’s a classic method. And the result is successful. It showed that using grammar translation method was good, especially used in Al - Islam Kartasura Junior High School. The score is higher than before using Grammar Translation Method. Their spirit and motivation also increased. They happy and enjoy in the English class. Therefore, it can be suggested for the other teacher that grammar translation method can be used as the alternative method in teaching which specially to improve grammar and vocabulary mastery.